Three Flavor Quasi-Dirac Neutrino Mixing, Oscillations and Neutrinoless Double Beta Decay - Amina Khatun (Symmetry, 2020)
The extension of the Standard model by three right-handed neutrino fields exhibit appealing symmetry between left-handed and right-handed sectors, which is only violated by interactions. It can accommodate three flavor quasi-Dirac neutrino mixing scheme, which allows processes with violation of both lepton flavor and total lepton number symmetries. We propose a <semantics>6×6</semantics> unitary matrix for parameterizing the mixing among three flavors of quasi-Dirac neutrino. This mixing matrix is constructed by two <semantics>3×3</semantics> unitary matrices that diagonalizes the Dirac mass term in the Lagrangian. By only assuming the Standard Model <semantics>V−A</semantics> weak interaction, it is found that probabilities of neutrino oscillations among active flavor states and effective masses measured by single beta decay, by neutrinoless double-beta decay and by cosmology only depend on single <semantics>3×3</semantics> unitary matrix relevant to mixing of active neutrino flavors. Further, by considering <semantics>1σ</semantics> and <semantics>3σ</semantics> uncertainties in the measured oscillation probability of electron antineutrino from reactor, derivation of the constraint on the Majorana neutrino mass component is demonstrated. The consequence for effective Majorana neutrino mass governing the neutrinoless double-beta decay is discussed.